2022
DOI: 10.2147/idr.s383444
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Resistance Prevalence of Helicobacter pylori Strains in Northwest China

Abstract: Purpose This study aims to estimate the resistance rate of Helicobacter pylori ( HP ) to commonly used antibiotics and analyze the potential influencing factors in northwest regions of China. Patients and Methods HP -positive patients visiting the outpatient department of multiple hospitals were enrolled in the study. Then, gastric mucosal biopsy specimens were collected for HP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…13 Some other studies reported a notably high secondary resistance rate to AMX, which indicated that previous treatment failure could be associated with AMX resistance. 31,38 In addition, the peptic ulcer seems a protective factor for the CLA and LEV resistance in this study. Patients with a peptic ulcer may have a timely treatment because of various symptoms and reduce the chance of biofilm formation which could resulted in antibiotic resistance.…”
Section: F I G U R Esupporting
confidence: 51%
“…13 Some other studies reported a notably high secondary resistance rate to AMX, which indicated that previous treatment failure could be associated with AMX resistance. 31,38 In addition, the peptic ulcer seems a protective factor for the CLA and LEV resistance in this study. Patients with a peptic ulcer may have a timely treatment because of various symptoms and reduce the chance of biofilm formation which could resulted in antibiotic resistance.…”
Section: F I G U R Esupporting
confidence: 51%
“…These results are consistent with a previous study conducted in northwest China. 15 Conversely, a study conducted in Chile reported an increase in the prevalence of LEV resistance with age in both men and women. 16 Notably, we did not observe a statistically significant difference in the prevalence of CLA resistance across different age groups.…”
Section: Discussionmentioning
confidence: 95%
“…China, too, confronts a significant challenge of antibiotic resistance, which presents grave implications for the effective treatment of H. pylori infections. (Zhong et al, 2021;Xu et al, 2022) Despite recent studies suggesting that high-dose dual therapy (HDDT) demonstrates similar effectiveness and adherence compared to bismuth-containing quadruple therapy (BQT) or standard triple treatment, BQT remains the predominant treatment approach for H. pylori infection in China (Chey et al, 2022;Zou et al, 2022). Nanjing, situated in eastern China, is a metropolis with a populace exceeding 10 million.…”
Section: Discussionmentioning
confidence: 99%